Teknologi Digital untuk Wisata Gastronomi - Ilma Pratiwi; Debi V. Br Bangun; Dewi Turgarini (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2021)
The development of digital technology which is rapidly growing provides great opportunities for entrepreneurs in the tourism sector to market their products and services digitally. In addition to reducing promotional costs, utilizing digital technology can also increase tourism marketing one step higher. Digital technology allows tourists to know clearly and completely related tourist destinations (DTW). Today's developing technology also provides opportunities for tourists to be able to enjoy and experience DTW directly from their respective homes with very real visuals. Social media, websites, AR and VR, provide opportunities for tourists to be able to get clearer information related to DTW. This study aims to determine how to optimize digital technology for gastronomic tourism.